UPAYA PENINGKATAN EKONOMI DAN PENGURANGAN SAMPAH DOMESTIK MASYARAKAT SUMBERSARI MELALUI PEMANFAATAN ALIRAN SUNGAI UNTUK BUDIDAYA IKAN MUJAIR - Romaidi, Romaidi; Prahardika, Bayu Agung; Hasyim, Muhammad Asmuni (JRCE (Journal of Research on Community Engagement), 2020)
One of the biggest threats from human activities to rivers is the increasing number of residential areas around or even just above the river flow. This condition is certainly very threatening the sustainability of rivers in the region. One of the biggest threats is that the garbage produced by the community will be directly disposed of in the river flow. One way that can be done to reduce waste disposal in the river is by utilizing river flow, so that many rivers are now increasingly being developed as a vehicle for habitat conservation, because the river is considered important for various aquatic plants, migratory and sedentary fishes, and aquaculture ponds, birds and several types of mammals. In this case, the concept of river management must be based on environmental, ecological, economic and social aspects according to the characteristics of the surrounding community. The purpose of this community service is to utilize river flow for tilapia fish farming. The method used in the service is the PAR by way of lectures and direct practice in aquaculture with karamba by utilizing river flow. From the results of community service including partners showed that some respondents know how to fish with karamba, but do not know that river flow can also be used for fish farming with the karamba system. As well as the results of fish farming practices with the karamba system most of the respondents agreed agree (73%) if the fish culture using the karamba system is used as an alternative business idea related to river flow utilization and 60% of respondents agree the use of river flow for fish cultivation can reduce waste disposal in the river.